2017
DOI: 10.3390/en10040518
|View full text |Cite
|
Sign up to set email alerts
|

How Smart LEDs Lighting Benefit Color Temperature and Luminosity Transformation

Abstract: Luminosity and correlated color temperature (CCT) have gradually become two of the most important factors in the evaluation of the performance of light sources. However, although most color performance evaluation metrics are highly correlated with CCT, these metrics often do not account for light sources with different CCTs. This paper proposes the existence of a relationship between luminosity and CCT to remove the effects of CCT and to allow for a fairer judgment of light sources under the current color perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The thermal behavior and the light depreciation along the LED life have also been improved thus making possible the construction of high power modules [2,3]. For example, there can be found currently in the market chip-on-board (COB) LED modules of more than 200 W. Another important feature of LEDs is their fast response and ease of control, enabling the implementation of complex control strategies [4][5][6]. All these improvements, combined with the continuous cost reduction that has taken place in recent years, have made LEDs the preferred choice for most lighting applications nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal behavior and the light depreciation along the LED life have also been improved thus making possible the construction of high power modules [2,3]. For example, there can be found currently in the market chip-on-board (COB) LED modules of more than 200 W. Another important feature of LEDs is their fast response and ease of control, enabling the implementation of complex control strategies [4][5][6]. All these improvements, combined with the continuous cost reduction that has taken place in recent years, have made LEDs the preferred choice for most lighting applications nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Their algorithm applies the DCT-STD and the DWT-STD for focus detection. Besides that, Chen et al have demonstrated a multi-spectral imaging method that can also show the color image reproduction [6][7][8]. While most previous methods for image combination employed a few inputs of different focal images, we attempt a new method for image composition using many input images.…”
Section: All-in-focused Image Combinationmentioning
confidence: 99%
“…Their algorithm applies the DCT-STD and the DWT-STD for focus detection. Besides that, Chen et al have demonstrated a multi-spectral imaging method that can also show the color image reproduction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been a strong effort for making lighting design [1][2][3][4] and corresponding lighting systems [5][6][7][8] sustainable and environmentally friendly [9] either by selecting efficient luminaires [10,11], lighting controls [12][13][14][15], or embodying more efficient lighting design [16][17][18] or daylight [19][20][21][22][23]. The importance of avoiding light pollution (LP) has gained interest in technical reports [24,25] and expert discussions [26] only in the last few years.…”
Section: Introductionmentioning
confidence: 99%